Independent Currency Authorities : An Analytic Primer - Osband, Kent.; Villanueva, Delano (Washington, D.C. : International Monetary Fund, 1992)
This paper provides an analytic overview of independent currency authorities (ICAs), sometimes called currency boards. ICAs issue and redeem domestic currency against an exchange standard on demand and back such operations through a 100 percent marginal foreign reserve cover. They also impose significant constraints on the banking system and the budget of the country that operates them. When supporting institutions have been put in place, ICAs appear to have promoted price stability, foreign trade, saving, and investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet